2020
DOI: 10.1186/s12933-020-01134-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucose variability and the risks of stroke, myocardial infarction, and all-cause mortality in individuals with diabetes: retrospective cohort study

Abstract: Background Previous research regarding long-term glucose variability over several years which is an emerging indicator of glycemic control in diabetes showed several limitations. We investigated whether variability in long-term fasting plasma glucose (FG) can predict the development of stroke, myocardial infarction (MI), and all-cause mortality in patients with diabetes. Methods This is a retrospective cohort study using the data provided by the Korean National Health Insurance Corporation. A total of 624,23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…Moreover, Coronary Artery Risk Development in Young Adults (CARDIA) study suggested that higher long-term FPG variability assessed by CV during young adulthood before the onset of diabetes was associated with incident diabetes, macrovascular events and mortality [ 53 ]. Recently, Lee et al showed that long-term FPG variability calculated by VIM was correlated with the risk of stroke, myocardial infarction, and all-cause mortality in patients with diabetes [ 54 ]. More importantly, the impact of FPG variability was higher in the elderly and those with a longer duration of diabetes and lower FPG levels.…”
Section: The Role Of Gv In Diabetic Macrovascular and Microvascular Cmentioning
confidence: 99%
“…Moreover, Coronary Artery Risk Development in Young Adults (CARDIA) study suggested that higher long-term FPG variability assessed by CV during young adulthood before the onset of diabetes was associated with incident diabetes, macrovascular events and mortality [ 53 ]. Recently, Lee et al showed that long-term FPG variability calculated by VIM was correlated with the risk of stroke, myocardial infarction, and all-cause mortality in patients with diabetes [ 54 ]. More importantly, the impact of FPG variability was higher in the elderly and those with a longer duration of diabetes and lower FPG levels.…”
Section: The Role Of Gv In Diabetic Macrovascular and Microvascular Cmentioning
confidence: 99%
“…Conversely, short-term glycemic variability (GV) includes an overall measure of intraday and between-day glucose fluctuations. Interestingly, GV demonstrated to add significant information, on top of HbA1c values, for the prediction of micro-and macrovascular complications, hypoglycemic episodes, and all-cause mortality in T2D patients [7][8][9][10]. Currently, no study has specifically investigated the effects of ranolazine on short-term GV.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested an adverse effect of high FBG variability on CVD in high risk populations, such as patients with diabetes or acute coronary syndrome [ 8 10 ]. However, whether high FBG variability can increase the risk of CVD in the general population remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…As an integral component of glucose homoeostasis, measuring FBG variability may be an essential addition to the use of FBG in clinical practice, and may contribute to identifying those at high risk of CVD [ 7 ]. A growing body of studies suggest that visit-to-visit FBG variability is an independent predictor of CVD events in patients with diabetes or with acute coronary syndrome [ 8 11 ], while evidence on the association between visit-to-visit FBG variability and CVD in the general population is limited [ 12 14 ]. Moreover, previous studies primarily estimated the short-term relative risk of CVD, which may not provide a comprehensive assessment for the overall burden of FBG variability on CVD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%